A cross-sectional community study of post-traumatic stress disorder and social support in Lao People's Democratic Republic - Bouavanh Southivong; Masao Ichikawa; Shinji Nakahara; Chanhpheng Southivong (The World Health Organization, 2013)
Objective To estimate post-traumatic stress disorder (PTSD) symptoms in those injured and not injured by landmines or unexploded ordnance (UXO) in rural Lao People's Democratic Republic and to determine whether the perception of social support was associated with PTSD symptom severity. Methods A community survey was conducted among 190 people injured by landmines or UXO and 380 age-, sex- and neighbourhood-matched non-injured individuals in the Sepone district of Savannakhet Province, the part of the Lao People's Democratic Republic most heavily bombed during the Viet Nam War. Using the Harvard Trauma Questionnaire and the Medical Outcomes Study Social Support Survey, trained health-care workers conducted face-to-face interviews to assess PTSD symptoms and level of perceived social support. Multiple linear regression was performed to explore the association between social support and other factors and PTSD. Findings The prevalence of PTSD was higher among the injured (10%) than among the non-injured (4%), but the level of perceived social support was not significantly different between the two groups. A higher level of perceived social support was associated with milder symptoms of PTSD. Women, older people and those with a formal education were more often and more severely affected by PTSD. Conclusion The perception of strong social support might help to alleviate the symptoms of PTSD among people injured by landmines or UXO in rural parts of the Lao People's Democratic Republic. Psychosocial interventions should be incorporated in assistance for the injured because they have more severe and longer-lasting symptoms of PTSD than the non-injured.